Bismuth-based composite high-temperature-resistant piezoelectric ceramic material and preparation method thereof

Through the design and preparation method of bismuth-based composite high-temperature resistant piezoelectric ceramic materials, combined with high-temperature secondary polarization and thermal cycling treatment, the existing bismuth layered piezoelectric ceramic materials have low piezoelectric activity and unstable electrical properties in high temperature environments, and the high voltage electroactiveness and high resistivity of ceramic materials at high temperatures are achieved.

CN119774997AActive Publication Date: 2025-04-08XI AN JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411955491.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-08
Estimated Expiration
2044-12-28

AI Technical Summary

Technical Problem

The existing bismuth layered piezoelectric ceramic materials have low piezoelectric activity in high temperature environments, coercive electric field and comprehensive electrical properties are unstable, and it is difficult to meet the working requirements in high temperature environments at the same time.

Method used

Bismuth-based composite high-temperature piezoelectric ceramic material is used, and the piezoelectric performance and high-temperature stability of ceramic materials are improved by high-temperature secondary polarization and thermal cycling treatment.

Benefits of technology

It realizes that ceramic materials have high voltage electroactivity, high resistivity and high temperature stability at high temperatures, and are suitable for applications at 500℃ or even higher temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774997A_ABST
    Figure CN119774997A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth-based composite high-temperature-resistant piezoelectric ceramic material and a preparation method thereof. The bismuth-based composite high-temperature-resistant piezoelectric ceramic material is formed by compounding Ca (1-x-y) (A1xA2y) Bi2 (Nb) (2-m-n) (B1mB2n) O9 bismuth layered structure piezoelectric ceramic with ultrahigh Curie temperature and (Na (0.5-p-q) A (3) pA (4) q) BiiNb2O9-based bismuth layered structure piezoelectric ceramic or bismuth-based perovskite structure high-temperature piezoelectric ceramic Bi (a) Pb (1-a) Zn (0.5 a) Ti (1-0.5 a) O3. The high-compactness composite ceramic material is obtained through the processes of powder pre-synthesis, mixing in proportion, ball milling, forming, oxygen feeding and sintering and the like. On the basis, the high-temperature-resistant piezoelectric composite ceramic material with high piezoelectric property, high resistivity, relatively low dielectric loss and high temperature stability is obtained by adopting a secondary polarization and secondary aging combined thermal cycle treatment process on the obtained ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric ceramic materials, and in particular relates to a bismuth-based composite high-temperature resistant piezoelectric ceramic material and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics are functional materials that can realize the mutual conversion of mechanical energy and electrical energy. PZT piezoelectric ceramics are the most typical piezoelectric materials. They have the characteristics of high piezoelectric coefficient and excellent mechanical quality factor. They have been widely used in ultrasonic devices, sensors, transducers and other fields. With the continuous development of science and technology, many fields such as energy, aerospace, and national defense industry have put forward huge application demands for piezoelectric materials that can work in high temperature environments. However, traditional PZT piezoelectric ceramics are prone to depolarization above 200°C and cannot meet the actual application needs. Therefore, it is of great value to study high-temperature piezoelectric ceramics that can be used in high-temperature environments.

[0003] Typical piezoelectric ceramic material systems include perovskite type, tungsten bronze type, bismuth layered type, etc. In comparison, bismuth layered piezoelectric ceramics have the advantages of high Curie temperature (usually >500°C), strong spontaneous polarization, low dielectric loss, high resistivity, and low aging rate, and have great application prospects in the fields of high-temperature vibration sensors. Common bismuth layered high-temperature piezoelectric systems include Bi4Ti3O 12 (The Curie temperature is about 637 °C, d 33 About 16 pC / N), Na 0.5 Bi 2.5 Nb2O9 (Curie temperature is about 776 ℃, d 33 About 10 pC / N), CaBi2Nb2O9 (Curie temperature is about 936 ℃, d 33 However, bismuth layered piezoelectric ceramics generally have disadvantages such as low piezoelectric activity and high coercive electric field, which makes it difficult to simultaneously meet the requirements of working in a suitable high temperature (500°C) environment and having stable comprehensive electrical properties.

[0004] In order to improve the electrical properties of bismuth layered piezoelectric ceramics, most current studies use ion doping or microstructure regulation to optimize performance. Ion doping can be used to appropriately reduce the oxygen vacancy concentration of the material, thereby increasing the resistivity or the spontaneous polarization strength of the material. Microstructure regulation is mainly achieved by controlling the grain size, or using a texturing process to arrange the ceramic grains in a certain orientation, thereby enhancing the piezoelectric performance in a specific direction. Although the above methods can improve the performance of piezoelectric ceramics, the process requirements are high, and the high-voltage electrical activity and high resistivity of the ceramic material are not stable enough at high temperatures. Therefore, how to obtain bismuth layered piezoelectric ceramic materials with high temperature stability, high-voltage electrical activity, and high resistivity is of great value. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the comprehensive electrical properties of piezoelectric ceramic materials in the prior art, the unstable high-temperature performance of the materials, and the inability to work stably for a long time in a high-temperature environment, and to provide a bismuth-based composite high-temperature resistant piezoelectric ceramic material having high-voltage electrical activity, high resistivity, and high temperature stability, and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution: A bismuth-based composite high-temperature resistant piezoelectric ceramic material, composed of bismuth layered piezoelectric ceramic Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9 and bismuth-based high temperature piezoelectric ceramic material M composite composition; A1 is Li, A2 is Nd or Sm, B1 is Mn, and B2 is W; wherein: x is 0.04 or 0.05; y is 0.04 or 0.05; m is 0.0025 or 0; and n is 0.0075 or 0.02.

[0007] Furthermore, the bismuth-based high-temperature piezoelectric ceramic material M is a bismuth layered piezoelectric ceramic (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 or Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3; A3 is alkali metal Li, A4 is Ce; p is 0.05; q is 0.05; i is 2.38; a is 0.35.

[0008] Furthermore, the chemical formula of the bismuth-based composite high temperature resistant piezoelectric ceramic material is: z1[Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9]-(1-z1)[(Na 0.5-p-q A3 p A4 q )Bi i Nb2O9] or z2 1-x-y (A1 x A2 y )Bi2(Nb)2-m-n (B1 m B2 n )O9]-(1-z2)[Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3], wherein z1 is 0.1 or 0.2; z2 is 0.9.

[0009] Furthermore, the bismuth-based composite high-temperature resistant piezoelectric ceramic material has a piezoelectric coefficient of (15-30) pC / N at room temperature, a room-temperature dielectric constant of 100-160 at 1 kHz, a room-temperature dielectric loss of 0.002-0.01 at 1 kHz, and a resistivity of (10 5 ~10 8 )Ωcm; the change rate of dielectric constant, dielectric loss and piezoelectric coefficient of bismuth-based composite high-temperature resistant piezoelectric ceramic material after 500 ℃ insulation treatment is less than 1%.

[0010] The above-mentioned method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material comprises the following steps: Step 1: Prefabricate Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n ) O9 ceramic powder: using various metal oxides, carbonates or nitrates as raw materials according to the chemical formula ratio, weighing, mixing, ball milling, drying, briquetting, calcining and crushing in sequence to obtain pre-synthesized powder; Step 2: Prefabrication (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 ceramic powder or Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3 ceramic powder: using various metal oxides, carbonates or nitrates as raw materials according to chemical formula ratio, weighing, mixing, ball milling, drying, briquetting, calcining and crushing to obtain pre-synthesized ceramic powder; Step 3, weighing the ceramic powder pre-synthesized in step 1 and step 2 according to the molar ratio of z: (1-z), ball milling and drying, and obtaining a powder having a medium particle size D50 of 1-2 microns, adding a binder to the powder, granulating and pressing to obtain a ceramic green sheet; Step 4, debinding the ceramic green sheet obtained in step 3 to obtain an intermediate product; Step 5, the intermediate product is spread on a pad, placed in an atmosphere furnace, and oxygen is introduced for sintering, the oxygen flow rate is 0.6-1.0 L / min, the sintering heating rate is 2-10 °C / min, the sintering temperature is 1050-1200 °C, the holding time is 1-4 hours, and after sintering, the furnace is cooled to obtain a ceramic material; Step 6: Polish the ceramic material on both sides, clean it and dry the printed electrode; Step 7, subjecting the prepared electrode ceramic material to a first polarization treatment; Step 8, performing a first aging treatment on the ceramic material after the first polarization; Step 9, subjecting the ceramic material after the first aging treatment to a second polarization treatment according to the same polarity as the first polarization treatment, wherein the second polarization temperature is 160-220° C., the polarization electric field is 120-220 kV / cm, and the polarization time is 20-60 minutes; Step 10, subjecting the ceramic material after the secondary polarization to a second aging treatment, wherein the second aging treatment is as follows: raising the temperature of the ceramic material after the second polarization from room temperature to 550-600°C, keeping the temperature for 24-48 hours, and then subjecting the ceramic material to 2-5 heating and cooling thermal cycle treatments from the current temperature to -60°C for 2-5 times, with a heating and cooling rate of 2-5°C / minute, to obtain a bismuth-based composite high temperature resistant piezoelectric ceramic material.

[0011] Furthermore, in step 5, the oxygen flow rate is 0.8 L / min, the sintering heating rate is 5 °C / min, and the sintering temperature is 1120 °C.

[0012] Furthermore, in step 6, when printing the electrode, the firing temperature of the electrode is 700-1000° C., and the holding time is 10-60 minutes.

[0013] Furthermore, in step 7, the polarization temperature during the first polarization treatment is 160-220° C., the polarization electric field is 120-220 kV / cm, and the polarization time is 20-60 minutes.

[0014] Furthermore, in step 8, the ceramic material after the first polarization is heated to 500-600° C., kept at this temperature for 24-48 hours, and then cooled to room temperature to complete the first aging treatment.

[0015] Furthermore, in step 10, the second aging treatment is: raising the temperature of the ceramic material after the second polarization from room temperature to 600°C, keeping it warm for 24 hours, and then performing two heating and cooling thermal cycle treatments from 600°C to -60°C, with a heating and cooling rate of 5°C / min, to obtain a bismuth-based composite high-temperature resistant piezoelectric ceramic material.

[0016] Compared with the prior art, the present invention has at least the following beneficial technical effects: The present invention combines CaBi2Nb2O9-based bismuth layered piezoelectric ceramics with high resistivity and low piezoelectric performance and modified Na 0.5 Bi 2.5 Nb2O9-based bismuth layered structure or Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3 bismuth-based perovskite structure high-temperature piezoelectric ceramic materials are compounded. Composite ceramics organically combine the advantages of high piezoelectricity and high resistivity of different materials, while weakening the respective shortcomings of the two raw materials, achieving complementarity and optimization between resistivity and piezoelectric properties, and can promote sintering to obtain high-density ceramic materials. Composite ceramics effectively improve the piezoelectric properties of ceramic materials and maintain high Curie temperature and high resistivity.

[0017] The preparation method of the bismuth-based composite high-temperature resistant piezoelectric ceramic material provided by the present invention adopts the method of passing oxygen during sintering. The oxygen passing at a certain flow rate effectively reduces the oxygen vacancies generated during the high-temperature sintering process of the ceramic material, thereby obtaining a ceramic material with high resistivity and high piezoelectricity at high temperature.

[0018] Furthermore, the present invention performs high-temperature secondary polarization, secondary aging and thermal cycle treatment on the basis of primary polarization of conventional piezoelectric ceramics, which can not only fully polarize the ceramic material to obtain a composite ceramic material with high voltage electrical properties, but also significantly improve the high-temperature stability of the dielectric and piezoelectric properties of the composite ceramic material. The developed ceramic material has good application prospects in the field of high-temperature piezoelectricity.

[0019] The preparation method of the present invention is easy to operate, is simpler than the high-temperature piezoelectric single crystal process, and is suitable for promotion and large-scale use.

[0020] After testing, the high-temperature piezoelectric composite ceramic material obtained by the present invention has the characteristics of good ceramic density, high piezoelectric coefficient, high high-temperature resistivity, high dielectric constant, low dielectric loss, and high Curie temperature. The composite ceramic material obtained by the present invention can be used to make ceramic components of different shapes and assembled into various piezoelectric sensors and transducers, which can be widely used in measurement, detection, control, etc. at 500°C or even higher temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of a method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material provided by the present invention; Figure 2 XRD patterns of the high temperature piezoelectric ceramics prepared in Examples 1 to 3; Figure 3The SEM scanning electron microscope images of the high temperature piezoelectric ceramics prepared in Examples 1 to 3; Figure 4 The resistivity of the high temperature piezoelectric ceramics prepared in Examples 1 to 3 varies with temperature. DETAILED DESCRIPTION

[0022] In order to make the purpose and technical solution of the present invention clearer and easier to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more. In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0024] A bismuth-based composite high-temperature resistant piezoelectric ceramic material is composed of a CaBi2Nb2O9-based bismuth layered structure piezoelectric ceramic and a bismuth-based high-temperature piezoelectric ceramic material M.

[0025] The chemical formula of the CaBi2Nb2O9-based piezoelectric ceramic is Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n)O9, wherein A1 is at least one of alkali metals Li, Na, K, A2 is at least one of rare earth elements Nd, Sm, Ce, Pr, La, Er, Tb, B1 is at least one of variable valence metals Mn, Ni, Co, Cu, and B2 is at least one of W and Mo. In the formula, x is 0.04 or 0.05; y is 0.04 or 0.05; m is 0.0025 or 0; and n is 0.0075 or 0.02.

[0026] One of the choices of Bismuth-based high temperature piezoelectric ceramic material M is modified Na 0.5 Bi 2.5 Nb2O9-based bismuth layered piezoelectric ceramics (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9. A3 is at least one of the alkali metals Li, Na, and K, and A4 is at least one of the rare earth elements Nd, Sm, Ce, Pr, La, Er, and Tb, wherein p is 0.05; q is 0.05; and i is 2.38.

[0027] The second choice of bismuth-based high-temperature piezoelectric ceramic material M is bismuth-based perovskite structure high-temperature piezoelectric ceramic Bi a Pb 1- a Zn 0.5a Ti 1-0.5a O3, where a is 0.35.

[0028] The third choice of bismuth-based high-temperature piezoelectric ceramic material M is bismuth-based perovskite structure high-temperature piezoelectric ceramic Bi b Pb 1- b Fe b Ti 1-b O3, where 0.6 <b≤1 。

[0029] Furthermore, the chemical formula of the composite high temperature piezoelectric ceramic material is: z1[Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9]-(1-z1)[(Na 0.5-p-q A3 p A4 q )Bi i Nb2O9] or z2[Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2n )O9]-(1-z2)[Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3], wherein z1 is 0.1 or 0.2, and z2 is 0.9.

[0030] A high temperature resistant piezoelectric composite ceramic material is prepared by the following method: Step 1: Prefabricate Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9 ceramic powder. According to the proportion shown in the chemical formula, various metal oxides, carbonates or nitrates with a purity of >99% are used as raw materials, weighed, mixed, ball-milled, dried, pressed into blocks, calcined and crushed to obtain pre-synthesized powder. The medium used for ball milling is anhydrous ethanol or deionized water. The calcination conditions are 700-1000℃ for 2-6 hours.

[0031] Step 2: Prefabrication (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 ceramic powder, Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3 ceramic powder or Bi b Pb 1-b Fe b Ti 1-b O3 ceramic powder. According to the proportion shown in the chemical formula, various metal oxides, carbonates or nitrates with a purity of >99% are used as raw materials, weighed, mixed, ball-milled, dried, pressed into blocks, calcined and crushed to obtain pre-synthesized ceramic powder. The medium used for ball milling is anhydrous ethanol. The calcination conditions are 600~1000 ℃ for 2~6 hours.

[0032] Step 3, the ceramic powder pre-synthesized in step 1 and step 2 is weighed according to the molar ratio of z: (1-z) and then ball-milled, and the value range of z is 0.1-0.2. The medium used for ball milling is anhydrous ethanol, and the ball milling time is 15-48 hours. After ball milling, the slurry is dried to obtain a powder with a medium particle size D50 of 1-2 microns. A polyvinyl alcohol solution with a concentration of 4%-10% is added to the dried powder as a binder, and granulation and pressing are performed to obtain a ceramic green sheet.

[0033] Step 4: Place the ceramic green sheet obtained in step 3 into an electric furnace for debinding treatment. The heating rate used for debinding is 2-8°C / min, the temperature is 400-700°C, and the holding time is 0.5-2 hours.

[0034] Step 5: Spread the debinded sample on an alumina or zirconia pad, and place it in an atmosphere furnace and introduce oxygen for sintering. The oxygen flow rate is 0.6-1.0 L / min, the sintering heating rate is 2-10 ℃ / min, the sintering temperature is 1050-1200 ℃, and the holding time is 1-4 hours. After sintering, cool it with the furnace to obtain a ceramic material.

[0035] Step 6: Double-sided polish the ceramic material after oxygen sintering, clean it, dry it and print the platinum electrode. The firing temperature of the platinum electrode is 700-1000°C, and the holding time is 10-60 minutes.

[0036] Step 7: subject the prepared electrode ceramic material to the first polarization treatment in high-temperature silicone oil, with a polarization temperature of 160-220°C, a polarization electric field of 120-220 kV / cm, and a polarization time of 20-60 minutes.

[0037] Step 8: Raise the temperature of the ceramic material after the first polarization to 500-600°C, keep it at that temperature for 24-48 hours, then cool it down to room temperature to complete the first aging treatment.

[0038] Step 9: Perform a secondary polarization treatment on the ceramic material after the first aging with the same polarity as the first polarization, with a polarization temperature of 160-220°C, a polarization electric field of 120-220 kV / cm, and a polarization time of 20-60 minutes. The purpose of the secondary polarization is to further improve the piezoelectric properties of the obtained piezoelectric ceramic material.

[0039] Step 10, subject the ceramic material after secondary polarization to a second aging treatment. The second aging process is to first increase the temperature from room temperature to 550-600 °C, keep the temperature for 24-48 hours, and then perform two heating and cooling thermal cycles from the temperature to -60 °C, with a heating and cooling rate of 2-5 °C / minute. The purpose of the second aging is to improve the high temperature stability of the electrical properties of the piezoelectric ceramic material and reduce the stress in the ceramic material.

[0040] Piezoelectric coefficient d of composite high temperature piezoelectric ceramic materials at room temperature 33 The room temperature dielectric constant ε is (15~30) pC / N at 1 kHz r The room temperature dielectric loss tanδ at 1 kHz is 0.002~0.01, and the resistivity at 450~500 ℃ is (10 5 ~10 8)Ωcm. The dielectric constant ε after heat treatment at 500℃ for 30 to 60 minutes r , dielectric loss tanδ and piezoelectric coefficient d 33 The rate of change is less than 1%.

[0041] Example 1 The bismuth-based composite high-temperature resistant piezoelectric ceramic material provided in this embodiment is: 0.2[(Ca 0.92 Li 0.04 Nd 0.04 )Bi2Nb 1.99 Mn 0.0025 W 0.0075 O9]-0.8[(Na 0.4 Li 0.05 Ce 0.05 )Bi 2.38 Nb2O9] composite ceramics, wherein the subscript numbers represent the molar ratio of the elements.

[0042] Reference Figure 1 The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material comprises the following steps: Step 1: 99% pure CaCO3, 99.9% Li2CO3, 99.99% Nd2O3, 99.9% Bi2O3, 99.99% Nb2O5, 99.9% MnO, 99.9% WO3 are mixed according to (Ca 0.92 Li 0.04 Nd 0.04 )Bi2Nb 1.99 Mn 0.0025 W 0.0075 The mixture was weighed in the proportion shown in Figure 10, and a certain proportion of zirconium balls were added. The mixture was milled for 20 hours using a planetary ball mill. The medium used for the milling was anhydrous ethanol. The mixture was dried, pressed into blocks, placed in an alumina crucible with a lid, and placed in a muffle furnace for calcination at 850°C for 4 hours. After cooling, the mixture was taken out and crushed to obtain Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9 ceramic powder.

[0043] Step 2: 99.9% pure Na2CO3, 99.9% pure Li2CO3, 99.99% pure CeO2, 99.9% pure Bi2O3, 99.99% pure Nb2O5, 0.4 Li 0.05 Ce 0.05 )Bi 2.38The mixture was weighed in the proportion shown in FIG. 1 , and a certain proportion of zirconium balls were added. The mixture was milled for 20 hours using a planetary ball mill. The medium used for the milling was anhydrous ethanol. The mixture was dried, pressed into blocks, placed in an alumina crucible with a lid, and placed in a muffle furnace for calcination at 850° C. for 3 hours. After cooling, the mixture was taken out and crushed to obtain (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 ceramic powder.

[0044] Step 3, weigh the ceramic powder pre-synthesized in step 1 and step 2 according to the molar ratio of 0.2:0.8 and put it into a ball mill, add a certain proportion of zirconium oxide balls and anhydrous ethanol for ball milling, and the ball milling time is 20 hours. After ball milling, the slurry is kept at 60°C for 24 hours to dry, and the medium particle size D50 of the obtained powder is less than 2 microns. Add a 5% polyvinyl alcohol solution as a binder to the dried powder, granulate and press to obtain a ceramic green sheet with a diameter of 12 mm.

[0045] Step 4: Place the ceramic green sheet obtained in step 3 into an electric furnace for debinding treatment. The heating rate used for debinding is 5°C / min, the temperature is 600°C, and the holding time is 1 hour.

[0046] Step 5: Spread the debinded sample on an alumina or zirconia pad and place it in an atmosphere furnace to introduce oxygen for sintering. The oxygen flow rate is 0.8 L / min, the sintering heating rate is 5 ℃ / min, the sintering temperature is 1120 ℃, and the holding time is 3 hours. After sintering, the ceramic material is cooled with the furnace. The powder X-ray diffraction results of the obtained composite ceramic material are shown in Figure 2 The surface morphology of the obtained ceramic material is shown in Figure 3 shown.

[0047] Step 6: Double-sided polishing of the oxygen-sintered ceramic material is performed, followed by ultrasonic cleaning. After cleaning, the ceramic material is dried at 120°C, and then the electrodes are printed using platinum slurry. The platinum electrode is fired at 800°C for 30 minutes to ensure good ohmic contact between the ceramic and the electrode.

[0048] Step 7: The prepared electrode ceramic material is subjected to the first polarization treatment in high-temperature silicone oil at a polarization temperature of 200°C, a polarization electric field of 150 kV / cm, and a polarization time of 30 minutes.

[0049] Step 8: Raise the temperature of the ceramic material after the first polarization to 500°C and keep it at this temperature for 24 hours to complete the first aging treatment.

[0050] Step 9: The ceramic material after the first aging is subjected to a second polarization treatment according to the same polarity as the first polarization, with a polarization temperature of 200°C, a polarization electric field of 200 kV / cm, and a polarization time of 30 minutes.

[0051] Step 10: The ceramic material after secondary polarization is subjected to a second aging process. The aging process is to first increase the temperature from room temperature to 600°C, keep the temperature for 24 hours, and then perform two heating and cooling thermal cycles from 600°C to -60°C, with a heating and cooling rate of 5°C / min.

[0052] The aged ceramic material was subjected to quasi-static 33 Tester, impedance analyzer to test its piezoelectric coefficient d 33 , Planar electromechanical coupling coefficient k p , dielectric constant ε r , dielectric loss tanδ, the results are shown in Table 1. The resistivity of ceramic materials at different temperatures was tested using a Keithley 6517B high resistance meter. The results are shown in Table 1. Figure 4 shown.

[0053] Example 2 The bismuth-based composite high-temperature resistant piezoelectric ceramic material provided in this embodiment is: 0.9[(Ca 0.92 Li 0.04 Nd 0.04 )Bi2Nb 1.99 Mn 0.0025 W 0.0075 O9]-0.1[(Na 0.4 Li 0.05 Ce 0.05 )Bi 2.38 Nb2O9] composite ceramics, wherein the subscript numbers represent the molar ratio of the elements.

[0054] A method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material comprises the following steps: Step 1: 99% pure CaCO3, 99.9% Li2CO3, 99.99% Nd2O3, 99.9% Bi2O3, 99.99% Nb2O5, 99.9% MnO, 99.9% WO3 are mixed according to (Ca 0.92 Li 0.04 Nd 0.04 )Bi2Nb 1.99 Mn 0.0025 W 0.0075The mixture was weighed in the proportion shown in Figure 10, and a certain proportion of zirconium balls were added. The mixture was milled for 20 hours using a planetary ball mill. The medium used for the milling was anhydrous ethanol. The mixture was dried, pressed into blocks, placed in an alumina crucible with a lid, and placed in a muffle furnace for calcination at 850°C for 4 hours. After cooling, the mixture was taken out and crushed to obtain Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9 ceramic powder.

[0055] Step 2: 99.9% pure Na2CO3, 99.9% pure Li2CO3, 99.99% pure CeO2, 99.9% pure Bi2O3, 99.99% pure Nb2O5, 0.4 Li 0.05 Ce 0.05 )Bi 2.38 The mixture was weighed in the proportion shown in FIG. 1 and a certain proportion of zirconium balls were added, and the mixture was milled for 20 hours using a planetary ball mill. The medium used for the milling was anhydrous ethanol. The mixture was dried, pressed into blocks, placed in an alumina crucible with a lid, and placed in a muffle furnace for calcination at 850 ° C for 3 hours. After cooling, the mixture was taken out and crushed to obtain (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 ceramic powder.

[0056] Step 3: The ceramic powder pre-synthesized in step 1 and step 2 is weighed in a molar ratio of 0.9:0.1 and placed in a ball mill, and a certain proportion of zirconium oxide balls and anhydrous ethanol are added for ball milling for 20 hours. After ball milling, the slurry is kept at 60°C for 24 hours for drying, and the obtained powder has a medium particle size D50 of less than 2 microns. A 5% polyvinyl alcohol solution is added to the dried powder as a binder, and granulation and pressing are performed to obtain a ceramic green sheet with a diameter of 8 mm.

[0057] Step 4: Place the ceramic green sheet obtained in step 3 into an electric furnace for debinding treatment. The heating rate for debinding is 5°C / min, the temperature is 600°C, and the holding time is 1 hour.

[0058] Step 5: Spread the debinded sample on an alumina or zirconia pad and place it in an atmosphere furnace to introduce oxygen for sintering. The oxygen flow rate is 0.8 L / min, the sintering heating rate is 5°C / min, the sintering temperature is 1120°C, and the holding time is 2 hours. After sintering, the ceramic material is cooled with the furnace. The powder X-ray diffraction results of the obtained ceramic material are as follows: Figure 2The surface morphology of the obtained ceramic material is shown in Figure 3 shown.

[0059] Step 6: Double-sided polishing of the oxygen-sintered ceramic material is performed, followed by ultrasonic cleaning. After cleaning, the ceramic material is dried at 120°C, and then the electrodes are printed using platinum slurry. The platinum electrode is fired at 800°C for 30 minutes to ensure good ohmic contact between the ceramic and the electrode.

[0060] Step 7: The prepared electrode ceramic material is subjected to the first polarization treatment in high-temperature silicone oil at a polarization temperature of 200°C, a polarization electric field of 150 kV / cm, and a polarization time of 30 minutes.

[0061] Step 8: Raise the temperature of the ceramic material after the first polarization to 500°C and keep it at this temperature for 24 hours to complete the first aging treatment.

[0062] Step 9: The ceramic material after the first aging is subjected to a second polarization treatment according to the same polarity as the first polarization, with a polarization temperature of 200°C, a polarization electric field of 200 kV / cm, and a polarization time of 30 minutes.

[0063] Step 10: The ceramic material after secondary polarization is subjected to a second aging process. The aging process is to first increase the temperature from room temperature to 600°C, keep the temperature for 24 hours, and then perform two heating and cooling thermal cycles from 600°C to -60°C, with a heating and cooling rate of 5°C / min.

[0064] The aged ceramic material was subjected to quasi-static 33 Tester, impedance analyzer to test its piezoelectric coefficient d 33 , Planar electromechanical coupling coefficient k p , dielectric constant ε r , dielectric loss tanδ, the results are shown in Table 1. The resistivity of ceramic materials at different temperatures was tested using Keithley 6517B high resistance meter. The results are shown in Table 1. Figure 4 shown.

[0065] Example 3 The bismuth-based composite high-temperature resistant piezoelectric ceramic material provided in this embodiment is: 0.9[(Ca 0.9 Li 0.05 Sm 0.05 )Bi2Nb 1.98 W 0.02 O9]-0.1[Bi 0.35 Pb 0.65 Zn 0.175 Ti 0.825 O3] composite ceramics, wherein the subscript numbers represent the molar ratio of the elements.

[0066] The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material comprises the following steps: Step 1: 99% pure CaCO3, 99.9% Li2CO3, 99.99% Sm2O3, 99.9% Bi2O3, 99.99% Nb2O5, 99.9% WO3 are mixed according to (Ca 0.9 Li 0.05 Sm 0.05 )Bi2Nb 1.98 W 0.02 The mixture was weighed in the proportion shown in Figure 10, and a certain proportion of zirconium balls were added. The mixture was milled for 20 hours using a planetary ball mill. The medium used for the milling was anhydrous ethanol. The mixture was dried, pressed into blocks, placed in an alumina crucible with a lid, and placed in a muffle furnace for calcination at 800°C for 4 hours. After cooling, the mixture was taken out and crushed to obtain Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9 ceramic powder.

[0067] Step 2: Mix 99.9% pure Bi2O3, 99% PbO, 99.9% ZnO and 99.9% TiO2 according to Bi 0.35 Pb 0.65 Zn 0.175 Ti 0.825 The mixture was weighed in the proportion shown in Figure 1, and a certain proportion of zirconium balls were added. The mixture was milled in a planetary ball mill for 16 hours. The medium used for the milling was anhydrous ethanol. The mixture was dried, pressed into blocks, placed in an alumina crucible with a lid, and placed in a muffle furnace for calcination at 800°C for 6 hours. After cooling, it was taken out and crushed to obtain Bi a Pb 1- a Zn 0.5a Ti 1-0.5a O3 ceramic powder.

[0068] Step 3: The ceramic powder pre-synthesized in step 1 and step 2 is weighed in a molar ratio of 0.9:0.1 and placed in a ball mill, and a certain proportion of zirconium oxide balls and anhydrous ethanol are added for ball milling for 20 hours. After ball milling, the slurry is kept at 60°C for 24 hours for drying, and the obtained powder has a medium particle size D50 of less than 2 microns. A 5% polyvinyl alcohol solution is added to the dried powder as a binder, and granulation and pressing are performed to obtain a ceramic green sheet with a diameter of 8 mm.

[0069] Step 4: Place the ceramic green sheet obtained in step 3 into an electric furnace for debinding treatment. The heating rate used for debinding is 5°C / min, the temperature is 600°C, and the holding time is 1 hour.

[0070] Step 5: Spread the debinded sample on an alumina or zirconia pad and place it in an atmosphere furnace to introduce oxygen for sintering. The oxygen flow rate is 0.8 L / min, the sintering heating rate is 5 ℃ / min, the sintering temperature is 1120 ℃, and the holding time is 2 hours. After sintering, the ceramic material is cooled with the furnace. The powder X-ray diffraction results of the obtained ceramic material are as follows: Figure 2 The surface morphology of the obtained ceramic material is shown in Figure 3 shown.

[0071] Step 6: Double-sided polishing of the oxygen-sintered ceramic material is performed, followed by ultrasonic cleaning. After cleaning, it is dried at 120°C, and then the electrodes are printed using platinum slurry. The platinum electrode is fired at 800°C for 30 minutes to ensure good ohmic contact between the ceramic and the electrode.

[0072] Step 7: The ceramic material of the prepared electrode is subjected to the first polarization treatment in high-temperature silicone oil, with the polarization temperature being 200° C., the polarization electric field being 130 kV / cm, and the polarization time being 30 minutes.

[0073] Step 8: Raise the temperature of the ceramic material after the first polarization to 500° C. and keep it at this temperature for 24 hours to complete the first aging treatment.

[0074] Step 9: The ceramic material after the first aging is subjected to a second polarization treatment according to the same polarity as the first polarization, with a polarization temperature of 200°C, a polarization electric field of 150 kV / cm, and a polarization time of 30 minutes.

[0075] Step 10: The ceramic material after secondary polarization is subjected to a second aging process. The aging process is to first increase the temperature from room temperature to 600°C, keep the temperature for 24 hours, and then perform two heating and cooling thermal cycles from 600°C to -60°C, with a heating and cooling rate of 5°C / min.

[0076] The aged ceramic material was subjected to quasi-static 33 Tester, impedance analyzer to test its piezoelectric coefficient d 33 , Planar electromechanical coupling coefficient k p , dielectric constant ε r , dielectric loss tanδ, the results are shown in Table 1. The resistivity of ceramic materials at different temperatures was tested using a Keithley 6517B high resistance meter. The results are shown in Table 1. Figure 4 shown.

[0077] Figure 2The XRD patterns show that the main phase of the ceramic material obtained in the present invention is a double-layer bismuth layered structure.

[0078] Figure 3 The results show that the obtained ceramic grains present a significant lamellar morphology, that is, the growth has significant anisotropy, because the growth rate of the grains in the direction perpendicular to the c-axis is significantly greater than that in the c-axis direction. In addition, the grains of the ceramic samples are fully developed and highly dense.

[0079] Figure 4 The results show that the high temperature resistivity of the composite ceramic material is low, and the resistivity of the ceramic at 500 °C is greater than 10 6 That is, the oxygen vacancies in the CaBi2Nb2O9-based bismuth layered piezoelectric ceramic material are effectively reduced through the composite ceramic method, and a ceramic material with good application prospects in the field of high-temperature piezoelectricity is obtained.

[0080] Table 1 shows the room temperature piezoelectric coefficients d of the high temperature piezoelectric ceramics obtained in Examples 1 to 3. 33 , Planar electromechanical coupling coefficient k p , dielectric constant ε r , dielectric loss tanδ, and the performance of the ceramic material after being heated at 500 °C for 30 minutes and then cooled to room temperature.

[0081] Table 1

[0082] Table 1 shows that the obtained composite ceramic material has good piezoelectric properties, high dielectric constant and low dielectric loss at room temperature. In addition, the piezoelectric and dielectric properties of the material changed less than 1% after heat treatment at 500 °C for 30 minutes. This shows that the composite ceramic material obtained by the secondary polarization process, the secondary aging process and the thermal cycle treatment process has good high-temperature stability. Therefore, the piezoelectric device made from this composite material has good application prospects at 500 °C or even higher temperatures.

[0083] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A bismuth-based composite high-temperature resistant piezoelectric ceramic material, characterized in that: The bismuth-based composite high-temperature resistant piezoelectric ceramic material comprises a bismuth layered structure piezoelectric ceramic Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9 and bismuth-based high temperature piezoelectric ceramic material M composite composition; A1 is Li, A2 is Nd or Sm, B1 is Mn, and B2 is W; wherein: x is 0.04 or 0.05; y is 0.04 or 0.05; m is 0.0025 or 0; and n is 0.0075 or 0.

02.

2. The bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 1, characterized in that: The bismuth-based high-temperature piezoelectric ceramic material M is a bismuth layered piezoelectric ceramic (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 or Bi a Pb 1-a Zn 0.5a Ti 1- 0.5a O3; A3 is alkali metal Li, A4 is Ce; p is 0.05; q is 0.05; i is 2.38; and a is 0.

35.

3. The bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 1, characterized in that: The chemical formula of the bismuth-based composite high temperature resistant piezoelectric ceramic material is: z1[Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9]-(1-z1)[(Na 0.5-p-q A3 p A4 q )Bi i Nb2O9] or z2 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n )O9]-(1-z2)[Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3], wherein z1 is 0.1 or 0.2; z2 is 0.

9.

4. The bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 1, characterized in that: The bismuth-based composite high-temperature resistant piezoelectric ceramic material has a piezoelectric coefficient of (15-30) pC / N at room temperature, a room-temperature dielectric constant of 100-160 at 1 kHz, a room-temperature dielectric loss of 0.002-0.01 at 1 kHz, and a resistivity of (10 5 ~10 8 )Ωcm; the change rate of dielectric constant, dielectric loss and piezoelectric coefficient of bismuth-based composite high-temperature resistant piezoelectric ceramic material after 500 ℃ insulation treatment is less than 1%.

5. The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 1, characterized in that: The following steps are involved: Step 1: Prefabricate Ca 1-x-y (A1 x A2 y )Bi2(Nb) 2-m-n (B1 m B2 n ) O9 ceramic powder: using various metal oxides, carbonates or nitrates as raw materials according to the chemical formula ratio, weighing, mixing, ball milling, drying, briquetting, calcining and crushing in sequence to obtain pre-synthesized powder; Step 2: Prefabrication (Na 0.5-p-q A3 p A4 q )Bi i Nb2O9 ceramic powder or Bi a Pb 1-a Zn 0.5a Ti 1-0.5a O3 ceramic powder: using various metal oxides, carbonates or nitrates as raw materials according to chemical formula ratio, weighing, mixing, ball milling, drying, briquetting, calcining and crushing to obtain pre-synthesized ceramic powder; Step 3, weighing the ceramic powder pre-synthesized in step 1 and step 2 according to the molar ratio of z: (1-z), ball milling and drying, and obtaining a powder having a medium particle size D50 of 1-2 microns, adding a binder to the powder, granulating and pressing to obtain a ceramic green sheet; Step 4, debinding the ceramic green sheet obtained in step 3 to obtain an intermediate product; Step 5, the intermediate product is spread on a pad, placed in an atmosphere furnace, and oxygen is introduced for sintering, the oxygen flow rate is 0.6-1.0 L / min, the sintering heating rate is 2-10 °C / min, the sintering temperature is 1050-1200 °C, the holding time is 1-4 hours, and after sintering, the furnace is cooled to obtain a ceramic material; Step 6: Polish the ceramic material on both sides, clean it and dry the printed electrode; Step 7, subjecting the prepared electrode ceramic material to a first polarization treatment; Step 8, performing a first aging treatment on the ceramic material after the first polarization; Step 9, subjecting the ceramic material after the first aging treatment to a second polarization treatment according to the same polarity as the first polarization treatment, wherein the second polarization temperature is 160-220° C., the polarization electric field is 120-220 kV / cm, and the polarization time is 20-60 minutes; Step 10, subjecting the ceramic material after the secondary polarization to a second aging treatment, wherein the second aging treatment is as follows: raising the temperature of the ceramic material after the second polarization from room temperature to 550-600°C, keeping the temperature for 24-48 hours, and then subjecting the ceramic material to 2-5 heating and cooling thermal cycle treatments from the current temperature to -60°C for 2-5 times, with a heating and cooling rate of 2-5°C / minute, to obtain a bismuth-based composite high temperature resistant piezoelectric ceramic material.

6. The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 4, characterized in that: In the step 5, the oxygen flow rate is 0.8 L / min, the sintering heating rate is 5 °C / min, and the sintering temperature is 1120 °C.

7. The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 4, characterized in that: In step 6, when printing the electrode, the firing temperature of the electrode is 700-1000° C., and the heat preservation time is 10-60 minutes.

8. The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 4, characterized in that: In step 7, the polarization temperature during the first polarization treatment is 160-220° C., the polarization electric field is 120-220 kV / cm, and the polarization time is 20-60 minutes.

9. The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 4, characterized in that: In step 8, the ceramic material after the first polarization is heated to 500-600° C., kept at this temperature for 24-48 hours, and then cooled to room temperature to complete the first aging treatment.

10. The method for preparing a bismuth-based composite high-temperature resistant piezoelectric ceramic material according to claim 4, characterized in that: In step 10, the second aging treatment is: raising the temperature of the ceramic material after the second polarization from room temperature to 600°C, keeping it warm for 24 hours, and then performing two heating and cooling thermal cycle treatments from 600°C to -60°C, with a heating and cooling rate of 5°C / min, to obtain a bismuth-based composite high-temperature resistant piezoelectric ceramic material.

Citation Information

Patent Citations

  • Bismuth laminar-structure piezoelectric ceramic and preparation method thereof, method for enhancing high-temperature resistivity of bismuth laminar-structure piezoelectric ceramic

    CN104725045A

  • Method for improving piezoelectric property and temperature stability of bismuth lamellar structure piezoceramic material

    CN104725078A

  • Thermal stable sodium niobate-based lead-free piezoelectric ceramic and preparation method thereof

    CN108689711A

  • Bismuth layered structure composite high-temperature piezoelectric ceramic material and preparation method thereof

    CN113979741A

  • Ceramic powder for processing copper-clad plate and preparation method thereof

    CN115215647A